Genetic resources as an object of international law - A. N. Vylegzhanin; P. V. Sotskova (Правоприменение)
The article examines whether the legal regime of genetic resources is outlined in the context of applicable rules relating to biological diversity. The purpose of the research is to confute the prospects for the formation of a universal legal regime for genetic resources, in the context of the draft UN Agreement on the Conservation and Sustainable Use of Marine Biological Diversity in Areas beyond National Jurisdiction, and the possibilities of using regional mechanisms in this domain.The methodology of the research includes the formal legal, comparative, historical, systemic and structural methods. The authors analyze and examine applicable international legal sources, including the 1992 Convention on Biological Diversity and its 2010 Nagoya Protocol. On the basis of the systemic and structural method the authors carry out the analysis of the sources of international law related to the conservation and sustainable use of genetic and other biological resources.The main results. The international community’s interest in genetic resources results from the growing need to take more informed environmental decisions. The relevant universal legal basis, created by the 1992 Convention on Biological Diversity, does not provide answers to some important questions, including the detailed legal definition of the term “genetic resources”, though the relevant definition contained in the 1992 Convention remains the only one that has been accepted by a large number of states. It is possible that states will be able to develop a more concrete legal rules relating to the genetic resources in the course of negotiating the UN Agreement on the Conservation and Sustainable Use of Marine Biological Diversity in Areas beyond National Jurisdiction. However, the development of such a universal international treaty might require a lot of effort in order to reconcile the divergent interests of states.Conclusions. Based on the analysis of applicable international law, the authors assert that the generally outlined legal basis for conservation of biodiversity, laid down by the 1992 Convention, demands further detailing in the modern context. The UN process on the conservation and sustainable use of marine biological diversity in areas beyond national jurisdiction is likely to take considerable efforts of participating actors before the appropriate legal mechanisms are agreed upon. So regional legal regimes might be an appropriate way to ensure the efficient management of genetic resources taking into account peculiarities of each individual region.